Extending HSI Test Generation Method for Software Product Lines - Fragal, Vanderson Hafemann; Simao, Adenilso; Mousavi, Mohammad Reza; Turker, Uraz Cengiz (Oxford Univ Press, 2019)
Featured Finite State Machines (FFSMs) were proposed as a modeling formalism that represents the abstract behavior of an entire software product line (SPL). Several model-based testing techniques have been developed to support test case generation for SPL specifications, but none support the full fault coverage criterion for SPLs at the family-wide level. In this paper, we propose an extension of the Harmonized State Identifiers (HSI) method, an FSM-based testing method supporting full fault coverage. By extending the HSI method for FFSMs, we are able to generate a single configurable test suite for groups of SPL products that can be instantiated using feature constraints. We implement a graphical tool named ConFTGen to guide the design, validation, derivation and test case generation for state, transition and full fault coverage of FFSMs. Experimental results indicate a reduction of approximately 50% on the number of test cases required to test 20 random SPL products. Also, we investigate the applicability of our method by applying it to a case study from the automotive domain, namely the Body Comfort System.
Keywords: formal modeling; test case generation; software product line; featured finite state machine